(3CKQ GdYhGed GdELJeGYjI ` GdEbJUGOjI hGdCefjI Ydi GdhVY GdJQHhj aj bVGA LRjf (B1975 (3` (B2004s - (3cQe, OfjRs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3eYgO GdYdhe GdGLJeGYjIs, 2004)
(3JgOa GdOQGSI Edi eYQaI eOi JCKQ GdJQHjI HGdYhGed GdeMjWI HgG, hPdc ef NdGd OQGSI CKQ GdYhGed GdGLJeGYjI GdGbJUGOjI hGdCefjI Ydi GdhVY GdJQHhj hGdJYdjej aj GdeOGQS GdQSejI hGdNGUI aj LRjf hefWbJgG aj aJQI eG bHd GdJMQjQ hHYO GdJMQjQ ef GdYGe (B1975 (3Edi (B2004. (3JYOOJ GdefGgL GdeJHYI aj GdOQGSI aGSJNOe GdefgL GdhUaj, GdJGQjNj, GdhKGFbj, GdEMUGFj, GdebGQfI, GdeSM, OQGSI GdMGdI, ceG hGSJYedJ COGI GdedGMXI, GdebGHdI, hGdGSJeGQI(B. (3hcGfJ GdYjfI YHGQI Yf SHY eOGQS QSejI heOQSJjf NGUJjf h(B50 (3YGFdI ef eNJda GdbQi GdLqRjfjI, eeKdI HCgGdj GdeSLdjf aj GdeOGQS, HGdEVGaI Edi eOQGA GdeOGQS GdehLhOjf aj LRjf hefWbJgG, GdPjf Je ELQGA ebGHdGJ eYge LejYkG(B. (3HjfJ GdfJGFL Cf GdJMQjQ bO ChLO hGbYkG JQHhjkG eZGjQkG heNJdakG Yf GdhVY GdPj cGf bGFekG CKfGA aJQI GdGMJdGd(B. (3SGge GdGSJbQGQ GdCefj HYO GdJMQjQ HTcd EjLGHj Ydi GdJdGePI, hGfNaVJ eYOdGJ GdQShH, abO cGfJ GdeOGQS GdQSejI aj Xd GdGMJdGd LGeOI dG JJbOe, HYcS GdeOGQS GdNGUI GdJj MQUJ Ydi GdGSJeQGQ hEYOGO CSGJPJgG hJhajQ GdhSGFd GdJQHhjI GddGReI NdGd aJQI GdGMJdGd hHYO GdJMQjQ(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Les Facteurs Socio- Economiques; Social and Economic Factors; (3GdYhGed GdGLJeGYjI hGdGbJUGOjIs; (3LRjfs